Silicon-carbon composite negative electrode material and preparation method and application thereof

By using silicon-carbon composite anode material composed of nano-silicon, porous hard carbon and porous metal in lithium-ion batteries, the problems of easy breakage and high volume expansion of silicon materials are solved, the energy density and cycle life of the battery are improved, and it is suitable for industrial production. .

CN119153670AInactive Publication Date: 2024-12-17GANZHOU LITAN NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202411640792.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Silicon materials are prone to shattering and have high volume expansion in the negative electrode materials of lithium-ion batteries, resulting in rapid attenuation of battery capacity, and it is difficult for the prior art to effectively improve energy density.

Method used

A silicon-carbon composite negative electrode material is used, composed of nano-silicon, porous hard carbon and porous metal. Through the high spherical shape and porosity design of carbon cladding and porous metal, the conductivity and deformation resistance are improved, and the charge and discharge capacity is reduced. resistance and volume expansion.

Benefits of technology

It significantly improves the first-time efficiency and cycle life of lithium-ion batteries, reduces the charging volume expansion and particle crushing rate, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153670A_ABST
    Figure CN119153670A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-carbon composite negative electrode material as well as a preparation method and application thereof, and relates to the technical field of electrode materials, the silicon-carbon composite negative electrode material sequentially comprises nano silicon, porous hard carbon, porous metal and a carbon coating layer from inside to outside; pores of the porous metal are filled with the porous hard carbon, and the nano silicon is distributed in the pores of the porous hard carbon; and the carbon coating layer is coated on the surfaces and pores of the porous metal and the porous hard carbon. The technical problems of low battery energy density and poor cycle performance caused by low conductivity, easy crushing and high charging volume expansion of the existing silicon-carbon negative electrode material are solved, the technical effects that the silicon-carbon negative electrode material has relatively high initial efficiency, relatively low charging volume expansion and relatively long cycle are achieved, and when the silicon-carbon negative electrode material is applied to the lithium ion secondary battery, the service life of the lithium ion secondary battery is prolonged. The first efficiency and the cycle life of the lithium ion battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to a silicon-carbon composite negative electrode material and a preparation method and application thereof. Background Art

[0002] At present, with the vigorous development of new energy electric vehicles, electronic consumer products and energy storage power stations, the demand for the energy density of lithium-ion battery negative electrodes is increasing. Among the many lithium-ion battery negative electrode materials, silicon materials have a high theoretical lithium storage capacity (forming Li at room temperature). 15 Si 4 , the theoretical capacity can reach 3579mA·h / g), which is close to 10 times the lithium storage capacity of the current commercial graphite negative electrode material (theoretical capacity 372mA·h / g), and is the most promising high-energy density lithium-ion battery negative electrode material for commercial mass production.

[0003] However, when silicon materials are actually used as negative electrode materials for lithium-ion batteries, the particles are easily broken when rolled. At the same time, silicon materials, as semiconductor materials, have low electrical conductivity. While having high capacity, they are accompanied by huge volume expansion during the charging and discharging process. These problems will cause the capacity of lithium-ion batteries to decay too quickly. At present, it is urgent to solve the above problems to improve the energy density of batteries.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] One of the purposes of the present invention is to provide a silicon-carbon composite negative electrode material having the advantages of higher initial efficiency, lower charging volume expansion and longer cycle.

[0006] The second object of the present invention is to provide a method for preparing a silicon-carbon composite negative electrode material, which has a simple process, high efficiency, high success rate and is suitable for industrial production.

[0007] The third object of the present invention is to provide an application of a silicon-carbon composite negative electrode material, which can effectively improve the initial efficiency and cycle life of a lithium-ion secondary battery.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: In the first aspect, a silicon-carbon composite negative electrode material comprises, from the inside to the outside, nano-silicon, porous hard carbon, porous metal and a carbon coating layer; The porous hard carbon is filled in the pores of the porous metal, and the nano-silicon is distributed in the pores of the porous hard carbon; The carbon coating layer is coated on the surface of the porous metal and porous hard carbon and in the pores thereof; The silicon-carbon composite negative electrode material is a spherical particle; The electrical conductivity of the silicon-carbon composite negative electrode material is greater than 40S / cm.

[0009] Furthermore, the average sphericity of the porous metal is greater than 0.95, the porosity of the porous metal is 20% to 60%, the pore size of the porous metal is 50nm to 1000nm, the particle size Dv10 of the porous metal is less than 2μm, the particle size Dv50 of the porous metal is less than 4μm, and the particle size Dv90 of the porous metal is less than 10μm.

[0010] Furthermore, the average sphericity of the particles of the silicon-carbon composite negative electrode material is ≥0.85; The number of particles of the silicon-carbon composite negative electrode material having a sphericity below 0.8 is ≤5%.

[0011] Furthermore, the particle size Dv10 of the silicon-carbon composite negative electrode material is less than 2 μm, the particle size Dv50 is less than 4 μm, and the particle size Dv90 is less than 10 μm.

[0012] Furthermore, the porous metal includes at least one of zirconium, copper, silver, titanium, germanium, platinum and nickel.

[0013] Furthermore, the average particle size of the nano-silicon is ≤10 nm.

[0014] Furthermore, the mass proportions of nano-silicon, porous hard carbon, porous metal and carbon coating layer in the silicon-carbon composite negative electrode material are 30%-60%, 20%-40%, 20%-40% and 0.5%-5% respectively.

[0015] In a second aspect, a method for preparing the silicon-carbon composite negative electrode material as described in any one of the above items comprises the following steps: (a) mixing a porous metal material and a water-soluble carbon source in water to react, thereby obtaining a porous metal filled with a hard carbon precursor, which is referred to as a first composite material; (b) subjecting the first composite material to carbonization pyrolysis and pore formation treatment to obtain a porous metal filled with porous hard carbon, which is referred to as a second composite material; (c) subjecting the second composite material to nano-silicon deposition and carbon coating to obtain the silicon-carbon composite negative electrode material.

[0016] A third aspect is an application of the silicon-carbon composite negative electrode material described in any one of the above items in a lithium-ion secondary battery.

[0017] Furthermore, the negative electrode sheet of the lithium-ion secondary battery comprises any of the above-mentioned silicon-carbon composite negative electrode materials; After the negative electrode sheet is rolled with a pressure of 50 tons, the breakage rate of particles in the negative electrode sheet is less than 5%.

[0018] Compared with the prior art, the present invention has at least the following beneficial effects: The silicon-carbon composite negative electrode material provided by the present invention has an interlayer of a porous metal material with good electrical conductivity, so that the electrical conductivity can be improved and the charge-discharge internal resistance can be reduced; at the same time, the porous metal material has a high deformation resistance, so that the problem of easy breakage of the material during rolling can be improved, and the volume expansion of the material during charging and discharging can be restrained, effectively alleviating the problem of excessive volume expansion during charging and discharging. A solvent thermal reaction is carried out through a soluble carbon source precursor, and the carbon source is dissolved into a liquid phase, and the liquid carbon source is distributed inside the porous metal for carbonization, so that the porous hard carbon is filled inside the porous metal, and the pore size of the porous metal material after the porous hard carbon is filled inside can reach less than 10nm, so nano-silicon is not easy to agglomerate and grow in the hole, and the expansion is small; at the same time, a solvent thermal reaction is used to fill the porous hard carbon inside the porous metal with high sphericity, the metal has a strong external compressive strength, the silicon-carbon material has no sharp parts, and the spherical particles are subjected to a more uniform force during the pole piece rolling process, the compressive strength is high, the particle breakage rate is low, and the side reaction is less, which is more conducive to improving the first efficiency of the silicon-carbon material. In summary, the silicon-carbon composite negative electrode material of the present invention has the advantages of higher initial efficiency, lower charging volume expansion and longer cycle. When applied to lithium-ion secondary batteries, it can effectively improve the initial efficiency and cycle life of lithium-ion batteries.

[0019] The preparation method of the silicon-carbon composite negative electrode material provided by the present invention comprises adding a porous metal material during the preparation of a hard carbon precursor, and then performing carbonization pyrolysis and pore-forming treatment, so that the hard carbon with a porous structure can be filled and distributed inside the porous metal material, thereby effectively enhancing the deformation resistance of the silicon-carbon composite negative electrode material and improving the electrical conductivity of the material; in short, the preparation method of the present invention is not only simple in process, efficient, and has a high success rate, and is suitable for industrial production, but also can improve the initial efficiency and cycle life of the silicon-carbon composite negative electrode material.

[0020] The application of the silicon-carbon composite negative electrode material provided by the present invention can effectively improve the initial efficiency and cycle life of the lithium-ion secondary battery, and has achieved outstanding application effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 This is a 5000-fold scanning electron microscope image of the silicon-carbon composite negative electrode material provided in Example 1 of the present invention; Figure 2 This is the first charge and discharge curve of the lithium button cell using the silicon-carbon composite negative electrode material obtained in Experimental Example 2 of the present invention. DETAILED DESCRIPTION

[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] According to a first aspect of the present invention, there is provided a silicon-carbon composite negative electrode material, which comprises nano-silicon, porous hard carbon, porous metal and a carbon coating layer in order from the inside to the outside; The porous hard carbon is filled in the porous metal pores, and the nano-silicon is distributed in the porous hard carbon pores; The carbon coating layer is coated on the surface of the porous metal and porous hard carbon and in the pores thereof; The silicon-carbon composite negative electrode material is spherical particles; The electrical conductivity of the silicon-carbon composite negative electrode material is >40S / cm.

[0025] In the present invention, porous hard carbon serves as the core of the nano-silicon volume expansion buffer substrate; porous metal material serves as an intermediate layer to restrain the volume expansion of nano-silicon particles and porous hard carbon particles and resist particle crushing; and the carbon coating layer is distributed on the surface of the porous metal material and porous hard carbon particles.

[0026] Porous hard carbon particles are distributed as core fillings inside porous metal materials. Porous hard carbon serves as a deposition carrier for nano-silicon particles. The porous hard carbon has a small pore size, which can not only reduce the agglomeration of nano-silicon particles, but also buffer the volume expansion of nano-silicon particles. At the same time, the carbon coating layer can isolate the nano-silicon particles from direct contact with water and electrolyte, reduce slurry gas production and side reactions, and is beneficial to improving the initial efficiency and cycle life of lithium-ion secondary batteries.

[0027] The silicon-carbon composite negative electrode material provided by the present invention has an interlayer of a porous metal material with good electrical conductivity, so that the electrical conductivity can be improved and the charge-discharge internal resistance can be reduced; at the same time, the porous metal material has a high deformation resistance, so that the problem of easy breakage of the material during rolling can be improved, and the volume expansion of the material during charging and discharging can be restrained, effectively alleviating the problem of excessive volume expansion during charging and discharging. A solvent thermal reaction is carried out through a soluble carbon source precursor, and the carbon source is dissolved into a liquid phase, and the liquid carbon source is distributed inside the porous metal for carbonization, so that the porous hard carbon is filled inside the porous metal, and the pore size of the porous metal material after the porous hard carbon is filled inside can reach less than 10nm, so nano-silicon is not easy to agglomerate and grow in the hole, and the expansion is small; at the same time, a solvent thermal reaction is used to fill the porous hard carbon inside the porous metal with high sphericity, the metal has a strong external compressive strength, the silicon-carbon material has no sharp parts, and the spherical particles are subjected to a more uniform force during the pole piece rolling process, the compressive strength is high, the particle breakage rate is low, and the side reaction is less, which is more conducive to improving the first efficiency of the silicon-carbon material. In summary, the silicon-carbon composite negative electrode material of the present invention has the advantages of higher initial efficiency, lower charging volume expansion and longer cycle. When applied to lithium-ion secondary batteries, it can effectively improve the initial efficiency and cycle life of lithium-ion batteries.

[0028] In a preferred embodiment, the average sphericity of the porous metal is greater than 0.95, and the high sphericity of the porous metal is beneficial to improving the sphericity of the silicon-carbon composite negative electrode material; the porosity of the porous metal is 20%~60%; if the porosity of the porous metal is too low, the proportion of nano-silicon in the pores that provides capacity is small, and the proportion of porous metal in the silicon-carbon composite negative electrode material is too large, which is not conducive to improving the energy density; if the porosity of the porous metal is too high, the compressive strength of the porous metal is weakened, the particle breakage rate becomes higher during the cold rolling process of the electrode piece, the side reactions increase, and the primary effect is reduced.

[0029] In a preferred embodiment, the pore size of the porous metal is 50nm~1000nm; if the pore size of the porous metal is too small, the preparation is difficult and the cost is high, which is not conducive to industrial production; if the pore size of the porous metal is too large, the compressive strength of the porous metal is weakened, and the porous hard carbon and nano-silicon are unevenly distributed, and the charging volume expands greatly.

[0030] In a preferred embodiment, the particle size of the porous metal is Dv10 <2μm, the particle size of the porous metal is Dv50 <4μm, and the particle size of the porous metal is Dv90 <10μm; if the particle size of the porous metal is too small, the particle size of the silicon-carbon composite negative electrode material will become smaller, the preparation difficulty will be high, the side reactions will increase, and the first effect will decrease; if the particle size of the porous metal is too large, the conductivity of the silicon-carbon composite negative electrode material will decrease, and the charging volume expansion will increase.

[0031] In the present invention, when more than 500 randomly selected particles of the silicon-carbon composite negative electrode material are measured, the average value of the particle sphericity is ≥0.85, and the number of particles with a sphericity below 0.8 is ≤5%.

[0032] In a preferred embodiment, the particle size Dv10 of the silicon-carbon composite negative electrode material is less than 2 μm, the particle size Dv50 is less than 4 μm, and the particle size Dv90 is less than 10 μm.

[0033] The particle size parameters of the silicon-carbon composite negative electrode material in the present invention are more conducive to further alleviating the problem of excessive volume expansion during charge and discharge, and further improving the cycle performance.

[0034] In a preferred embodiment, the porous metal includes but is not limited to at least one of zirconium, copper, silver, titanium, germanium, platinum and nickel, which is more conducive to further improving the electrical conductivity of the material, reducing the internal resistance of charge and discharge, and further improving the problem of easy breakage of the material during rolling, and further alleviating the problem of excessive volume expansion during charge and discharge.

[0035] In a preferred embodiment, the average particle size of nano-silicon is ≤10nm, and its typical but non-limiting average particle size is, for example, 10nm, 9nm, 8nm, 7nm, 6nm, 5nm, 4nm, 3nm, 2nm, and 1nm, which is more conducive to further improving the cycle performance.

[0036] In the present invention, the mass proportions of nano-silicon, porous hard carbon, porous metal and carbon coating layer in the silicon-carbon composite negative electrode material are 30%-60%, 20%-40%, 20%-40% and 0.5%-5% respectively.

[0037] According to a second aspect of the present invention, there is provided a method for preparing any one of the silicon-carbon composite negative electrode materials, comprising the following steps: (a) mixing a porous metal material and a water-soluble carbon source in water to react, thereby obtaining a porous metal filled with a hard carbon precursor, which is referred to as a first composite material; (b) carbonizing and pyrolyzing the first composite material and forming pores to obtain a porous metal filled with porous hard carbon, which is recorded as a second composite material; (c) The second composite material is subjected to nano-silicon deposition and carbon coating treatment to obtain a silicon-carbon composite negative electrode material.

[0038] The present invention provides a method for preparing a silicon-carbon composite negative electrode material. In the process of preparing a hard carbon precursor, a porous metal material is added. Then, through carbonization pyrolysis and pore-forming treatment, the hard carbon with a porous structure can be filled and distributed inside the porous metal material, thereby effectively enhancing the deformation resistance of the silicon-carbon composite negative electrode material and improving the electrical conductivity of the material.

[0039] A typical method for preparing a silicon-carbon composite negative electrode material comprises the following steps: (a) mixing a porous metal material and a water-soluble carbon source in pure water and heating them to react, thereby obtaining a porous metal composite material filled with a hard carbon precursor, which is recorded as a first composite material; (b) subjecting the first composite material to high-temperature carbonization and pyrolysis, pore formation and pulverization treatments in sequence to obtain a porous metal composite material filled with porous hard carbon, which is referred to as a second composite material; (c) The second composite material is contacted with a silane compound (nano-silicon deposition raw material) and an organic carbon source (carbon coating layer raw material) in sequence for pyrolysis to obtain a silicon-carbon composite negative electrode material.

[0040] In summary, the preparation method of the present invention is not only simple in process, efficient, and has a high success rate, and is suitable for industrial production, but also can improve the initial efficiency and cycle life of the silicon-carbon composite negative electrode material.

[0041] According to a third aspect of the present invention, there is provided a use of any of the above-mentioned silicon-carbon composite negative electrode materials in a lithium-ion secondary battery.

[0042] The application of the silicon-carbon composite negative electrode material provided by the present invention can effectively improve the initial efficiency and cycle life of the lithium-ion secondary battery, and has achieved outstanding application effects.

[0043] In a preferred embodiment, the negative electrode sheet of a lithium-ion secondary battery comprises any one of the above-mentioned silicon-carbon composite negative electrode materials.

[0044] After the negative electrode sheet made of the silicon-carbon composite negative electrode material of the present invention is rolled at a pressure of 50 tons, more than 500 particles are randomly extracted from the negative electrode sheet, and the particle breakage rate is less than 5%.

[0045] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0046] Example 1 A method for preparing a silicon-carbon composite negative electrode material comprises the following steps: S1: 4 kg of glucose, 0.5 kg of spherical porous copper metal and 12 kg of pure water were mixed in a reactor and reacted at 200° C. for 4 h to obtain a porous metal composite material filled with a hard carbon precursor, which was recorded as the first composite material; S2: In a mixed atmosphere of 90% nitrogen and 10% water vapor, the porous metal composite material (first composite material) of step S1 is subjected to carbonization pyrolysis and pore-forming treatment in a rotary kiln, wherein the temperature of carbonization pyrolysis is 900°C and the time of carbonization pyrolysis is 10 hours, and then crushed to obtain a porous metal composite material filled with porous hard carbon, which is recorded as the second composite material; S3: The porous metal composite material (second composite material) of step S2 was pyrolyzed with monosilane and acetylene in a rotary furnace at 500°C for 5h to obtain a silicon-carbon composite negative electrode material. Its physical and chemical index parameters are shown in Table 1, and its 5000x scanning electron microscope image is shown in Figure 1 .

[0047] Example 2 The difference between this embodiment and embodiment 1 is that in step S1, glucose is replaced by rice starch, and the porous copper metal is replaced by porous nickel metal; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon composite negative electrode material, and its physical and chemical index parameters are shown in Table 1.

[0048] Example 3 The difference between this embodiment and embodiment 1 is that in step S1, glucose is replaced by sucrose, and the porous copper metal is replaced by porous platinum metal; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon composite negative electrode material, and its physical and chemical index parameters are shown in Table 1.

[0049] Example 4 The difference between this embodiment and embodiment 1 is that in step S2, the carbonization pyrolysis time of 10 h is replaced by 12 h, and the pyrolysis at 500 °C for 5 h in step S3 is replaced by pyrolysis at 500 °C for 6 h; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon composite negative electrode material, and its physical and chemical index parameters are shown in Table 1.

[0050] Example 5 The difference between this embodiment and embodiment 1 is that in step S1, glucose is replaced by resorcinol, 12 kg of pure water is replaced by 1 kg of pure water, 3 kg of formaldehyde, 2 kg of ammonia water and 6 kg of ethanol, and the reaction temperature of 200° C. is replaced by 40° C.; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon composite negative electrode material, and its physical and chemical index parameters are shown in Table 1.

[0051] Comparative Example 1 The difference between this comparative example and Example 1 is that in step S1, porous copper metal is not added; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon composite negative electrode material, and its physical and chemical index parameters are shown in Table 1.

[0052] Comparative Example 2 The difference between this comparative example and Example 1 is that in step S1, pure water is not added when the materials are mixed, but the materials are mixed in solid phase and reacted at a temperature of 200° C. for 4 h; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon composite negative electrode material, and its physical and chemical index parameters are shown in Table 1.

[0053] Comparative Example 3 The difference between this embodiment and embodiment 1 is that in step S3, pyrolysis for 5 h is replaced by pyrolysis for 10 h; The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon composite negative electrode material, and its physical and chemical index parameters are shown in Table 1.

[0054] Comparative Example 4 Prior art CN 115911326 A discloses a method for preparing a silicon-carbon composite material, comprising the following steps: (1) adding porous carbon, porous metal oxide and dispersant into an organic solvent, dispersing them uniformly, and spray drying them to obtain a carbon-based composite precursor; (2) placing the carbon-based composite precursor prepared in step (1) in a vapor deposition furnace, introducing an inert protective gas to remove the air in the tube, and then introducing silane gas for calcination to obtain a nano-silicon deposited carbon-based composite material; (3) Using a plasma method, the nano-silicon deposited carbon-based composite material prepared in step (2) is transferred to an inductively coupled plasma reaction device, and an ammonia / carbon source mixed gas is introduced into the cavity of the inductively coupled plasma reaction device for deposition to obtain a nitrogen-carbon coated nano-silicon porous carbon composite material.

[0055] Compared with the present invention, on the one hand, the comparative example uses metal oxides to form a carbon-based composite precursor, and then prepares a silicon-carbon composite material. Due to the poor electrical conductivity of metal oxides, the powder electrical conductivity of the obtained silicon-carbon composite material is significantly lower than that of the composite material of the present invention, which will cause the internal resistance of the battery to be large, reach the cut-off voltage in advance, and greatly reduce the specific capacity and cycle performance; on the other hand, the comparative example uses spray drying to combine the porous carbon and the porous metal oxide, which belongs to solid-phase mixed bonding, which will cause the porous carbon to be unable to be filled into the interior of the porous metal oxide. At the same time, due to the large pore size of the porous metal oxide (20nm-100nm), nano-silicon is easy to agglomerate and grow, resulting in increased expansion. The present invention uses a soluble carbon source precursor to carry out a solvent thermal reaction, and the carbon source is dissolved into a liquid phase. The liquid carbon source is distributed inside the porous metal for carbonization, so that the porous hard carbon is filled inside the porous metal, and the internal filling The pore size of the porous metal material filled with porous hard carbon can reach below 10nm, so nano-silicon is not easy to agglomerate and grow in the pores, and the expansion is small. At the same time, the metal material wraps the porous hard carbon and nano-silicon on the outside, and has strong anti-expansion ability, which further reduces the expansion. In addition, since the comparative example uses a spray drying method, the resulting silicon-carbon material has an irregular morphology, and its particles have sharp edges with weak compressive resistance, which is easily crushed during the electrode rolling process, resulting in increased side reactions, lower initial efficiency (89%-90%), and lower gram capacity (1540mAh / g-1580mAh / g). The present invention uses solvent thermal reaction to fill porous hard carbon inside a highly spherical porous metal. The metal has strong compressive resistance on the outside, the silicon-carbon material has no sharp parts, and the spherical particles are subjected to more uniform force during the electrode rolling process, have high compressive resistance, low particle breakage rate, and fewer side reactions, which is more conducive to improving the initial efficiency of the silicon-carbon material.

[0056] Test Example 1 The physical and chemical index parameters of the silicon-carbon composite negative electrode materials obtained in Examples 1-5 and Comparative Examples 1-3 are shown in Table 1.

[0057] The silicon content of the material was tested using the CS-3000G tester. The particle size (μm) range of the material was tested using Dandong Better Laser Particle Sizer BT-9300ST; The conductivity of the powder was measured using GEST-126; Field emission scanning electron microscopy (JSM-7800F) was used to analyze the morphology and pattern processing of the materials; The sphericity of the material was measured using Dandong Better Dynamic Image Particle Size and Shape Analyzer BT-1700.

[0058] Table 1

[0059] As can be seen from Table 1, the conductivity of the silicon-carbon composite negative electrode material is determined by the type of porous metal material and the silicon content. In Examples 1-3, when the silicon content is basically the same, the conductivity of the silicon-carbon composite negative electrode material is determined by the conductivity of the porous metal material; the conductivity of the metal copper used in Example 1 is the largest, so the conductivity of the obtained silicon-carbon composite negative electrode material is the largest; in Comparative Example 1, no porous metal material is added, so the conductivity of the negative electrode material is the lowest; in Example 4, the carbonization pore-forming time is long, the silicon deposition time is long, the silicon content is high, and the silicon-carbon composite negative electrode The electrical conductivity of the material is slightly low. In Example 5, the hard carbon yield is high after carbonization of the phenolic resin, and the silicon content is lower under the same preparation process, so the electrical conductivity of the silicon-carbon composite negative electrode material is relatively high; the electrical conductivity of the negative electrode material obtained in Comparative Example 2 is lower than that of the negative electrode material in Examples 1-5. The main reason is that solid phase mixing is used in Comparative Example 2, resulting in low sphericity and large particle size, which leads to uneven distribution of the combination of porous metal material and porous hard carbon material; Comparative Example 3 has the highest silicon content, and the proportion of porous metal material is too low, so the electrical conductivity of the negative electrode material is relatively low.

[0060] Test Example 2 The first reversible capacity and first efficiency of the obtained silicon-carbon composite negative electrode material were tested as follows: Silicon-carbon composite negative electrode material, conductive carbon black and binder are mixed in pure water at a mass ratio of 94.5:1.5:4, homogenized, and the solid content is controlled to be 48wt%, coated on a copper foil current collector, vacuum-baked at 100°C for 8h, pressed and formed, and then punched to prepare a negative electrode sheet; The button half-cell was assembled in an argon-filled glove box. The counter electrode was a metal lithium sheet, the separator was PE, and the electrolyte was 1 mol / L LiPF 6 EC / DMC (Vol 1:1); The button cell was charged and discharged. The test process was 0.2C DC to 0V, 0.05C DC to 0V, 0V CV50μA, 0.01C DC to 0V, 0V CV 20μA, Rest 10min, 0.2C CC to 1.5V. The first reversible capacity and first efficiency of the silicon-carbon composite negative electrode material were measured; Among them, the button battery testing equipment is the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.

[0061] The expansion rate test of silicon-carbon composite negative electrode material S600 is as follows: The silicon-carbon composite negative electrode material is measured for the first reversible capacity by the above-mentioned charge-withdrawal test method, and then a certain amount of the same graphite negative electrode is mixed according to the calculation to mix the silicon-carbon composite negative electrode material to 600±5mA·h / g, abbreviated as S600; S600 mixed material, conductive carbon black and binder (mass ratio 92:2:6) were homogenized in pure water, the solid content was controlled to 48wt%, and the mixture was coated on a current collector with a copper foil as the substrate, and then vacuum baked at 90°C for 8h, pressed by a roller press, and then sliced ​​by a slicing device to prepare a negative electrode sheet; the thickness of the negative electrode sheet was measured with a micrometer, recorded as T1, and the thickness of the substrate was measured as T2, and the data were recorded; The button half-cell was assembled in a glove box filled with argon. The counter electrode was a metal lithium sheet, the diaphragm was made of PE, and the electrolyte was 1 mol / L LiPF 6 EC / DMC (Vol 1:1); charge and discharge test of button cell, test process 0.1CDC to 0.005V, 0.05C DC to 0.005V, 0.02C DC to 0.005V, Rest 10min, 0.1C CC to1.5V, 0.1C DC to 0.005V, 0.05C DC to 0.005V, 0.02C DC to 0.005V; measure the first reversible capacity and efficiency of negative electrode material; The battery is disassembled, and the thickness of the negative electrode material obtained by the disassembly is detected and recorded as T3; the first full-charge expansion data of the negative electrode material is calculated according to the formula F=(T3-T1) / (T1-T2), and F is the first full-charge expansion rate; Among them, the button battery testing equipment is the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.; the slicing equipment is the MSK-T10 button half-cell slicing equipment of Kejing; the micrometer detection equipment is Japan's Mitutoyo 293-100-10; and the rolling equipment is the MSK-HRP-05 button half-cell slicing equipment of Kejing.

[0062] Capacity retention rate test, the method is as follows: The silicon-carbon composite negative electrode material powder was mixed with the graphite negative electrode (mass ratio of 10-80:20-90) to obtain a mixed negative electrode powder. Then, the negative electrode powder, Super p and BP-7 were mixed in pure water at a mass ratio of 92:4:4, and the solid content was controlled at 48wt%. After homogenization, it was coated on a current collector with a copper foil as the substrate, placed in a vacuum baking oven at 90°C for 4 hours, and the pole piece was cold pressed using a commercial roller pressing equipment of Kejing. The pole piece was sliced ​​into small discs with a diameter of 22mm using a commercial slicing equipment of Kejing to prepare a negative electrode pole piece; commercial 523 positive electrode material, SP and PVDF (polyvinylidene fluoride) were mixed into an appropriate amount of NMP (N-methylpyrrolidone) at a mass ratio of 90:7:3. The mixed slurry was mixed with 1% pyrrolidone (2% pyrrolidone) solvent, the solid content was controlled to be 55wt%, the mixed slurry was coated on the current collector with aluminum foil as the substrate, placed in a vacuum oven at 120℃ for 4h, the pole piece was cold pressed with a commercial roller pressing equipment of Kejing, and the pole piece was sliced ​​into small discs with a diameter of 22mm using a commercial slicing equipment of Kejing to prepare the positive pole piece; dried at 85℃ under vacuum (-0.1MPa) for 8h, weighed and calculated the weight of the active material; the separator used was PE, and the electrolyte was 1mol / L LiPF 6 EC / DMC (Vol 1:1); assembled into CR2430 button-type full cells in a glove box; The button-type full battery was left to stand at room temperature for 2 hours, activated by charge and discharge at 0.1C on the Blue Electric test system, and then cycled at 1C (voltage range of 3.0~4.2V) for 500 cycles; the capacity retention rate of the material = discharge capacity of the last cycle / discharge capacity of the first cycle × 100%.

[0063] The above test results are shown in Table 2, and the first charge and discharge curve of the lithium button battery of the silicon-carbon composite negative electrode material of Example 1 is shown in Figure 2 .

[0064] Table 2

[0065] As can be seen from Table 1 and Table 2, the negative electrode materials obtained in Examples 1-5 have a lower percentage of broken particles, the reason being that the porous metal material with a spherical structure is distributed outside the nano-silicon particles and hard carbon particles, and has a higher compressive resistance; the negative electrode material obtained in Comparative Example 1 is easier to break and has poor conductivity because it has no metal material to resist pressure; the porous metal material, porous hard carbon material and nano-silicon particles in Comparative Example 2 are unevenly distributed, resulting in the metal material being unable to effectively protect the nano-silicon particles and hard carbon material, resulting in a higher particle breakage rate of the negative electrode material and poor conductivity; the negative electrode material obtained in Comparative Example 3 has a higher silicon content, resulting in a relatively low mass proportion of the metal material, resulting in weaker conductivity and compressive resistance of the material. At the same time, the first efficiency, S600 first expansion rate and cycle capacity retention rate of the batteries made of the negative electrode materials obtained in Examples 1-5 are all good, mainly because the broken particle rate of the silicon-carbon composite negative electrode material is low and has strong compressive resistance.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A silicon-carbon composite negative electrode material, It is characterized in that From the inside to the outside, it includes nano-silicon, porous hard carbon, porous metal and carbon coating layer; The porous hard carbon is filled in the pores of the porous metal, and the nano-silicon is distributed in the pores of the porous hard carbon; The carbon coating layer is coated on the surface of the porous metal and porous hard carbon and in the pores thereof; The silicon-carbon composite negative electrode material is a spherical particle; The electrical conductivity of the silicon-carbon composite negative electrode material is greater than 40S / cm.

2. The silicon-carbon composite negative electrode material according to claim 1, It is characterized in that The average sphericity of the porous metal is greater than 0.95, the porosity of the porous metal is 20% to 60%, the pore size of the porous metal is 50nm to 1000nm, the particle size Dv10 of the porous metal is less than 2μm, the particle size Dv50 of the porous metal is less than 4μm, and the particle size Dv90 of the porous metal is less than 10μm.

3. The silicon-carbon composite negative electrode material according to claim 1, It is characterized in that The average sphericity of the particles of the silicon-carbon composite negative electrode material is ≥0.85; The number of particles of the silicon-carbon composite negative electrode material having a sphericity below 0.8 is ≤5%.

4. The silicon-carbon composite negative electrode material according to claim 1, It is characterized in that The particle size of the silicon-carbon composite negative electrode material is Dv10<2μm, the particle size is Dv50<4μm, and the particle size is Dv90<10μm.

5. The silicon-carbon composite negative electrode material according to claim 1, It is characterized in that The porous metal includes at least one of zirconium, copper, silver, titanium, germanium, platinum and nickel.

6. The silicon-carbon composite negative electrode material according to claim 1, It is characterized in that The average particle size of the nano-silicon is ≤10nm.

7. The silicon-carbon composite negative electrode material according to any one of claims 1 to 6, It is characterized in that The mass proportions of nano-silicon, porous hard carbon, porous metal and carbon coating in the silicon-carbon composite negative electrode material are 30%-60%, 20%-40%, 20%-40% and 0.5%-5% respectively.

8. A method for preparing the silicon-carbon composite negative electrode material according to any one of claims 1 to 7, It is characterized in that The following steps are involved: (a) mixing a porous metal material and a water-soluble carbon source in water to react, thereby obtaining a porous metal filled with a hard carbon precursor, which is referred to as a first composite material; (b) subjecting the first composite material to carbonization pyrolysis and pore formation treatment to obtain a porous metal filled with porous hard carbon, which is referred to as a second composite material; (c) subjecting the second composite material to nano-silicon deposition and carbon coating to obtain the silicon-carbon composite negative electrode material.

9. Use of the silicon-carbon composite negative electrode material according to any one of claims 1 to 7 in a lithium-ion secondary battery.

10. The use according to claim 9, It is characterized in that The negative electrode sheet of the lithium-ion secondary battery comprises the silicon-carbon composite negative electrode material; After the negative electrode sheet is rolled with a pressure of 50 tons, the breakage rate of particles in the negative electrode sheet is less than 5%.

Citation Information

Patent Citations

  • Low-expansion long-life silicon-carbon composite material and preparation method thereof

    CN115911326A

  • Preparation method of silicon-carbon composite material and silicon-carbon composite material

    CN116314671A

  • Silicon-based composite material, preparation method and battery

    CN116864643A

  • Silicon-carbon composite material, preparation method thereof, negative plate and secondary battery

    CN118198312A

  • Silicon-carbon negative electrode material, preparation method and battery

    WO2024193118A1

Cited By

  • Gradient pyrolysis dual-pore-forming silicon-carbon negative electrode material and preparation method thereof

    CN121085244A